Dios Como Atracción Y Rechazo - Merino, José Antonio (Miscellanea francescana, 2017)
Presently, we observe a great interest for religion and the question of God's existence with several treatises on "atheism" and "atheology" [antagonism to theology]. Concern for religion comes from far and wide, but in our time it is the basis for an ethics to be able to live freely. This is neither a surprise nor an originality, because the tension between belief and disbelief is profoundly a cultural issue. The difference is in the way and the assumption of doing so. It insists on the death, the exile and the silence of God. God belongs to the structure of the human being. Therefore one can say that man is a seeker or a tempter of God.